An ex ante evaluation of the Revenu de Solidarité Active by micro-macro simulation techniques - Luciano Canova; Luca Piccoli; Amedeo Spadaro (IZA Journal of European Labor Studies, 2015)
This paper aims to investigate the effects of the introduction of an active welfare state measure in France, the Revenu de Solidarité Active, which replaced the old system of social minima. By using a micro-macro simulation model, we characterize the effects on households' disposable income, labor supply, wages, GDP, public deficit, and other micro and macroeconomic aspects. Our findings suggest that although increasing public expenditure, the reform largely repays its cost by reducing involuntary unemployment, increasing labor supply and private consumption and thus improves GDP and the deficit/GDP ratio. If the great recession did not occur, poverty and inequality would have been significantly reduced by the RSA reform.
Keywords: I38; C63; C68; J22; H31; 330; Revenue de Solidarité active; RSA; Active welfare state; Microsimulation; CGE; Micro-macro; Labour supply; Policy evaluation